Clinicopathological correlation of malignant skin tumors: A retrospective study of five years. - Rajbhar, Rahul; Anvikar, Arti; Sulhyan, Kalpana (International Journal of Health Sciences, 2020)
Objective: Skin cancers are relatively uncommon malignancies worldwide, but there is a progressive increase in the incidence over the last few decades. Materials and Methods: We have studied the clinical and histopathological features of malignant skin tumors received in the department of pathology of our tertiary care institute over a period of 3 years and 8 months. A detailed analysis of clinical, gross, and microscopic findings was performed, followed by clinicopathological correlation. Results: One hundred and one specimens of skin tumors were received during this period, of which 37 (36.27%) were malignant tumors. Keratinocytic tumors were most common (81.08%) followed by appendageal tumors (10.81%). Squamous cell carcinoma (SCC) was the most frequent malignancy followed by basal cell carcinoma (BCC). Malignant melanoma, hidradenocarcinoma, malignant proliferating trichilemmal tumor (MPTT), sebaceous carcinoma, and fibrosarcomatous dermatofibrosarcoma were also observed. Variants such as hybrid verrucous SCC, basosquamous carcinoma, infiltrating BCC, and MPTT with spindle SCC were also found. Malignant skin tumors were most frequent in the seventh decade (40.54%). Males and females were almost equally affected. Overall, head and neck region was the most common site for malignant skin tumors. Conclusion: The vast diversity of skin tumors produces difficulty in diagnosis. Any lesion, for which the diagnosis is uncertain, based on the history and clinical examination, should be biopsied for histopathological examination to rule out malignancy.